Business Skills, Corporate Governance, and Competitiveness of Small Businesses in South Africa - Nkwinika, Sthembiso Eugine Rodney; Obokoh, Lawrence O. (International Review of Management and Marketing, 2024)
This study investigates the relationship between small business competitiveness, business skills, and corporate governance in South Africa. Business skills deficiency hinders the competitiveness of SMMEs in South African manufacturing. The SMME sector continues to operate in a highly unpredictable market due to the skills gap; this significantly affects small businesses’ competitiveness. The high failure rate of small businesses in South Africa is partly attributed to the skills gap and poor corporate governance practices. Resources need to be adequately managed in small businesses, contributing to subpar performance. The study adopted a quantitative research approach. Survey Monkey collected data from 462,972 small business owners or managers. The collected data were analysed using SPSS. The study’s findings revealed that small businesses’ competitiveness in their early years of operation is interdependent on good governance practices such as strategy, risks, and stakeholder interactions, which have been highlighted as a tool to enhance the sustainability of small businesses in South Africa. The study concludes that business skills associated with corporate governance improve small businesses’ competitiveness in their early years of operation. The study recommends that to boost their competitiveness and sustainability in South Africa, small businesses should supplement with proper corporate governance practices, such as strategy, reporting, risks, and stakeholder interactions.